EXPLORATION OF TEENAGERS' PERCEPTIONS OF CONTEMPORARY BATIK DESIGN INNOVATION - Nabila Alfadwa, Isna; Sunarya, I Ketut; Susanto, Moh. Rusnoto (Yayasan Education and Social Center, 2025)
This research aims to explore teenager’s perceptions of contemporary batik design innovation, with a focus on teenagers aged 15-19 years in high schools in the city of Yogyakarta. The method used is qualitative, where data is collected through structured interviews with 20 informants selected purposively. The research results show that teenagers have diverse views regarding contemporary batik, where aesthetic factors, self-identity and the influence of globalization play an important role in their interest. In addition, this research identifies the challenges faced in integrating traditional and modern elements in batik design, as well as the importance of community experience in the batik making process. It is hoped that these findings can provide practical recommendations for craftsmen and communities to attract the younger generation's interest in batik, as well as become the basis for further research on batik and the younger generation. Thus, this research contributes to the understanding of how innovation in batik design can accommodate the needs and tastes of the younger generation, as well as strengthen the sustainability of Indonesia's cultural heritage.